Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 13 - Cumulative Review - Page 970: 47


{$\frac{-1 + i\sqrt {35}}{6},\frac{-1 - i\sqrt {35}}{6}$}

Work Step by Step

$p=-3p^{2}-3$ can be rearranged as $3p^{2}+p+3=0$ Now solving $3p^{2}+p+3=0$: Step 1: Comparing $3p^{2}+p+3=0$ to the standard form of a quadratic equation $ax^{2}+bx+c=0$; $a=3$, $b=1$ and $c=3$ Step 2: The quadratic formula is: $x=\frac{-b \pm \sqrt {b^{2}-4ac}}{2a}$ Step 3: Substituting the values of a,b and c in the formula: $x=\frac{-(1) \pm \sqrt {1^{2}-4(3)(3)}}{2(3)}$ Step 4: $x=\frac{-1 \pm \sqrt {1-36}}{6}$ Step 5: $x=\frac{-1 \pm \sqrt {-35}}{6}$ Step 6: $x=\frac{-1 \pm \sqrt {-1\times35}}{6}$ Step 7: $x=\frac{-1 \pm \sqrt {-1}\times\sqrt {35}}{6}$ Step 8: $x=\frac{-1 \pm i\sqrt {35}}{6}$ Step 9: $x=\frac{-1 + i\sqrt {35}}{6}$ or $x=\frac{-1 - i\sqrt {35}}{6}$ Step 10: Therefore, the solution set is {$\frac{-1 + i\sqrt {35}}{6},\frac{-1 - i\sqrt {35}}{6}$}.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.